2023
DOI: 10.1186/s41182-023-00546-4
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical presentation, and predictors of outcome in nontuberculous mycobacterial central nervous system infection: a systematic review

Durga Shankar Meena,
Deepak Kumar,
Vasudha Meena
et al.

Abstract: Background CNS manifestations represent an emerging facet of NTM infection with significant mortality. Due to protean presentation and low index of suspicion, many cases are often treated erroneously as tubercular meningitis or fungal infections. Objectives Literature on NTM CNS disease is scarce, with most available data on pulmonary disease. This systematic review aimed to evaluate the epidemiology, clinical presentation, diagnostic modalities, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The NTM infection has a poor prognosis, with a mortality rate estimated at 32–39.3% among HIV patients [ 5 , 12 ], which illustrates the pathogen’s invasiveness and ineffective treatment methods. A recent systematic review of NTM CNS infections reported a 37.5% case fatality rate; although this review did not include any M. genavense cases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The NTM infection has a poor prognosis, with a mortality rate estimated at 32–39.3% among HIV patients [ 5 , 12 ], which illustrates the pathogen’s invasiveness and ineffective treatment methods. A recent systematic review of NTM CNS infections reported a 37.5% case fatality rate; although this review did not include any M. genavense cases [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our review of the literature, cases span from the 1960s to the present. By the end of December 2023, there were 114 cases of intracranial NTM infection reported or summarized in the literature (5,6,(8)(9)(10)(11)(12)(13)(14)(15)(16)(21)(22)(23)(24)(25)(26)(27). Antonia Flor et al reported two cases and identified 50 cases of NTM meningitis in the English-language literature before 1994 (8).…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In general, patients with Mycobacterium fortuitum infection tend to have a lower death rate and may exhibit less drug resistance when compared to those with Mycobacterium abscessus (5). Previous literature also indicated that a high CSF protein level is a risk factor for poor outcomes (27). However, further exploration and data accumulation is required to know whether intracranial infection caused by Mycobacterium rhodesiae could have a better outcome and exhibit less drug resistance as compared to other species.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Mycobacterium avium complex (MAC) was the most common etiology, followed by M. fortuitum and M. abscesses (34.8%, 21.4%, and 15.2%, respectively). The overall case fatality rate was 37.5% [ 2 ]. Since the prevalence of acquired immunodeficiency syndrome (AIDS), NTM infection has increased [ 3 ].…”
Section: Introductionmentioning
confidence: 99%